Whizzy Busy People - Parker, Guy (Orchard Books)
Tom and Millie try to find out what the best job in the world could be! Tom and Millie want the best job in the world when they grow up. Will they be a nurse like Mommy, a fireman like Daddy, or a pilot like Auntie Alice?